Antiviral Medication in Sexually Transmitted Diseases. Part II: HIV - Majewska, Anna; Mlynarczyk-Bonikowska, Beata; Malejczyk, Magdalena; Mlynarczyk, Grazyna; Majewski, Slawomir (Mini Reviews in Medicinal Chemistry, 2015)
This is a second part of a review under a main title Antiviral medication in sexually transmitted diseases. In the part we published in Mini Rev Med Chem. 2013,13(13):1837-45, we have described mechanisms of action and mechanism of resistance to antiviral agents used in genital herpes and genital HPV infection. The Part II review focuses on therapeutic options in HIV infection. In 1987, 6 years after the recognition of AIDS, the FDA approved the first drug against HIV - zidovudine. Since then a lot of antiretroviral drugs are available. The most effective treatment for HIV is highly active antiretroviral therapy - a combination of several antiretroviral medicines that cause a reduction of HIV blood concentration and often results in substantial recovery of impaired immunologic function. At present, there are over 20 drugs licensed and used for the treatment of HIV/AIDS, and these drugs are divided into one of six classes. Investigational agents include GS-7340, the prodrug of tenofovir and BMS-663068 - the first in a novel class of drugs that blocks the binding of the HIV gp120 to the CD4 receptor.
Keywords: inhibitors